COMPARATIVE STUDIES ON ANTIOXIDANT AND ANTIMICROBIAL PROPERTIES OF GRAPE AND PAPAYA SEED EXTRACTS USING IN-VITRO STUDIES - FAISAL RS,; RAJU CV,; LAKSHMISHA IP,; RAJKUMAR RS,; SABA KK, (International Journal of Pharma and Bio Sciences, 2015)
In the present study, antioxidant and antimicrobial activities of Grape seed extract (GSE) and Papaya seed extract (PSE) were investigated by using different in-vitro models viz., DPPH radical activity, ABTS scavenging activity, metal chelation, ferric reducing power, linoleic acid model and antimicrobial activity by disc diffusion method. The GSE contained four times higher phenolic and six times higher total flavonoid content compared to PSE. The extracts showed dose dependent ferric reducing ability with a very good correlation to total phenolic content (r2 = 0.96). The linoleic acid model system with 5 days of incubation showed that the addition of GSE and PSE to the reaction mixture inhibited peroxidation by 81.2 and 61.5 % respectively. GSE showed higher antimicrobial activity on gram-positive strains compared to PSE. These findings suggest that, the GSE is a cheap and promising source of potent in-vitro antioxidant and antimicrobial activities.